Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/pbc.24794
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of a multi‐agent oral antiangiogenic (metronomic) regimen in children with recurrent or progressive cancer

Abstract: BackgroundPreclinical models show that an antiangiogenic regimen at low-dose daily (metronomic) dosing may be effective against chemotherapy-resistant tumors. We undertook a prospective, open-label, single-arm, multi-institutional phase II study to evaluate the efficacy of a “5-drug” oral regimen in children with recurrent or progressive cancer.ProcedurePatients ≤21 years old with recurrent or progressive tumors were eligible. Treatment consisted of continuous oral celecoxib, thalidomide, and fenofibrate, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(141 citation statements)
references
References 30 publications
4
127
0
Order By: Relevance
“…Promising results were recently reported for a metronomic chemotherapy protocol in the treatment of recurrent embryonal brain tumors (46). It took more than ten years to empirically and incrementally develop the sophisticated 8-drug combination regimen based on the results of previous pre-clinical and clinical studies (4749). By involving clinicians, biologists and modelers throughout the entire process, our workflow has the potential to significantly reduce the time required to develop optimal metronomic protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results were recently reported for a metronomic chemotherapy protocol in the treatment of recurrent embryonal brain tumors (46). It took more than ten years to empirically and incrementally develop the sophisticated 8-drug combination regimen based on the results of previous pre-clinical and clinical studies (4749). By involving clinicians, biologists and modelers throughout the entire process, our workflow has the potential to significantly reduce the time required to develop optimal metronomic protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Antiangiogenic agents such as bevacizumab have also failed to control recurrent ependymomas [ 21 ]. Metronomic therapy has shown some benefi t in selected cases [ 22 ]. Recent drug screen in preclinical models have shown that 5-FU may be an option [ 23 ].…”
Section: Relapse Strategymentioning
confidence: 98%
“…This study will evaluate the use of biweekly IV bevacizumab in combination with five oral drugs (thalidomide, celecoxib, fenofibrate, and alternating cycles of daily low-dose oral etoposide and cyclophosphamide), augmented with alternating courses of intrathecal etoposide and liposomal cytarabine. The primary objective of the MEMMAT trial was to evaluate the efficacy of this multidrug anti-angiogenic approach in this heavily pre-treated patient population [115]. Additionally, safety and tolerability data was also further assessed.…”
Section: Symposiamentioning
confidence: 99%